Saving the Fundaments: Impact of a Military Coup on the Sudan Health System - Alhadi K. Osman; Mona Ibrahim; Mohamed Elsheikh; Karrar Karrar; Hassan Salih (Sudan Journal of Medical Sciences)
Military coups are not uncommon occurrences, particularly in developing nations where political systems might be less firmly entrenched or still evolving. Developments of this nature can often have profound implications for the affected nation’s healthcare systems, both in the immediate aftermath and over the longer term. This paper narrates some notable consequences of political instability on the national health system, particularly placing them in the context of the military coup in October 2021 – emphasizing the context behind the political turbulence, its acute and direct consequences, and the possible long-term legacies of political shocks on the already overwhelmed health system. As a descriptive piece, this narrative does not only look at the impact of the military coup on hospitals, but considers the implications for the healthcare system as defined by the WHO, with particular emphasis on the impact of the coup on health funding from multi-laterals, service delivery, human resource availability, and supply chains in Sudan.